2015
DOI: 10.18632/oncotarget.3446
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase CK2 is widely expressed in follicular, Burkitt and diffuse large B-cell lymphomas and propels malignant B-cell growth

Abstract: Serine-threonine kinase CK2 is highly expressed and pivotal for survival and proliferation in multiple myeloma, chronic lymphocytic leukemia and mantle cell lymphoma. Here, we investigated the expression of α catalytic and β regulatory CK2 subunits by immunohistochemistry in 57 follicular (FL), 18 Burkitt (BL), 52 diffuse large B-cell (DLBCL) non-Hodgkin lymphomas (NHL) and in normal reactive follicles. In silico evaluation of available Gene Expression Profile (GEP) data sets from patients and Western blot (WB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…Several investigators reported that CK2 is overexpressed and activated in a variety of hematological malignancies such as multiple myeloma (40, 41), mantle cell lymphoma (40, 41), follicular lymphoma (42), diffuse large B-cell lymphoma (42), acute B-lymphoblastic leukemia (4345), and CLL (4649). These observations led to the development of CK2 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators reported that CK2 is overexpressed and activated in a variety of hematological malignancies such as multiple myeloma (40, 41), mantle cell lymphoma (40, 41), follicular lymphoma (42), diffuse large B-cell lymphoma (42), acute B-lymphoblastic leukemia (4345), and CLL (4649). These observations led to the development of CK2 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…CK2 is upregulated as an oncogene in many human cancers including kidney (27), breast (28), and other cancers (29, 30). CK2 inhibitors have been actively tested in multiple cancer types in preclinical and clinical trials (30).…”
Section: Discussionmentioning
confidence: 99%
“…Pioneering work in mouse models demonstrated that CK2 overexpression may synergize with alterations of FasL, TP53, and c‐Myc in sustaining lymphocyte growth or malignant phenotype . Subsequent work has shown that CK2 is overexpressed in human aggressive lymphomas: a panel of 103 GC‐derived NHL was analyzed by immunohistochemistry for the expression of CK2α and CK2β . The two subunits were found on average markedly expressed across all the NHL subtypes, with Burkitt lymphomas displaying the highest protein levels.…”
Section: Ck1 and Ck2 In Lymphoid Malignanciesmentioning
confidence: 98%